2023
DOI: 10.3389/fphar.2022.1096055
|View full text |Cite
|
Sign up to set email alerts
|

HIPPO signaling-related signature for predicting prognosis and therapeutic response in gastric cancer

Abstract: Background: Gastric cancer (GC) is a multifactorial progressive disease with high mortality and heterogeneous prognosis. Effective prognostic biomarkers for GC were critically needed. Hippo signaling pathway is one of the critical mechanisms regulating the occurrence and development of GC, and has potential clinical application value for the prognosis and treatment of GC patients. However, there is no effective signature based on Hippo signaling pathway-related genes (HSPRGs) to predict the prognosis and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…One of the main issues is that people with cervical cancer are increasingly becoming resistant to the medications used in chemotherapy. For this reason, choosing the right chemotherapy medications is crucial to the customized care of patients with stomach cancer 25 . Subsequently, anti-cancer medications were chosen for this study in order to evaluate drug susceptibility in both high-risk and low-risk populations.…”
Section: Results Of Drug Sensitivity Analysismentioning
confidence: 99%
“…One of the main issues is that people with cervical cancer are increasingly becoming resistant to the medications used in chemotherapy. For this reason, choosing the right chemotherapy medications is crucial to the customized care of patients with stomach cancer 25 . Subsequently, anti-cancer medications were chosen for this study in order to evaluate drug susceptibility in both high-risk and low-risk populations.…”
Section: Results Of Drug Sensitivity Analysismentioning
confidence: 99%
“…A previous study demonstrated that patients with high DLG3 expression in the breast showed worse survival[ 14 ]. In gastric cancer, Rui Jiang et al[ 15 ] found that DLG3 was correlated with sensitivity of some chemotherapeutic drugs (such as paclitaxel). However, its value in predicting pCR is not clear.…”
Section: Introductionmentioning
confidence: 99%